Evaluasi Efektivitas Program Pembelajaran Jarak Jauh di Sekolah Menengah Atas pada Masa Pandemi Covid-19 - Iqbal, Muhammad; Marsyela, Marsyela; Marsyeli, Marsyeli; Hasanah , Uswatun; Br Lubis, Melati; Khofifah Siregar, Nur (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to describe and explain literature studies regarding the concepts of evaluation, effectiveness, and distance learning during the COVID-19 pandemic. Evaluating the effectiveness of distance learning programs in high schools during this period is particularly relevant due to the significant changes in teaching methods. This study employs a library research method, involving a comprehensive review of books and journal articles. The research process includes collecting articles, reducing and analyzing them, and drawing conclusions. Findings indicate that assessing the effectiveness of distance learning programs is crucial to determine the extent to which learning objectives were achieved during the COVID-19 pandemic. The goal of this research is to enhance the effectiveness of distance learning programs in high schools during the pandemic